Motivasi Berlatih Ditinjau dari Perbandingan Sosial dan Regulasi Diri pada Atlet Karate - Yunnanda Anggun Apriliyani; Ridwan Budi Pramono (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
This study aims to determine the relationship between social-comparison and self-regulation with motivation to practice in karate athletes. Practicing is very important for karate athletes to improve their abilities.Â  This study used a quantitative method with 84 participants. The measuring instrument used is social-comparison scale (Î± = 0.866), self-regulation scale (Î± =0.845), and motivation to practice scale (Î±=0.886). The results of the major hypothesis showed that there was a relationship between social-comparison and self-regulation with motivation to practice (p=0,000; r=0.658). The results of the minor hypothesis test one show that there is a positive relationship between social-comparison and motivation to practice (p=0.000; r=0.615). These results are the same with the second minor hypothesis on the variable self-regulation and motivation to practice (p=0.000; r=0.592). The results of this research will provide benefits in the development of psychology, especially in the field of sports psychology. Help karate athletes and coaches to obtain information to increase motivation to practice.